NEW PACT ON MIGRATION AND ASYLUM OF THE EUROPEAN UNION - Трнавац, Милутин (Political Review, 2024)
This paper analyses the latest normative solutions of the European Union in the areas of migration and asylum. The most important activities of the European Union in these areas, which previously influenced the adoption of new normative acts with the aim of ensuring the safety and well-being of people seeking international protection and a better life, are presented. In this sense, a detailed overview of all the regulations adopted by the European Union, which compose the new Pact on Migration and Asylum, is given. The analysis also includes a special review of new normative solutions, as well as a comparative view with the previous versions of the European Union regulations in these areas. The focus of the paper is on the analysis of the reform of the entire European framework for managing asylum and migration in order to establish safer external borders, faster and more efficient procedures for asylum, as well as a more fair and efficient system of solidarity and responsibility.
Keywords: migrations; asylum; European Union; Pact on Migration and Asylum; regulation; directive